Changes in the internal movement structure during the push and paddle phases in Olympic national team lugers - Gołaś, Artur; Drozd, Miłosz; Krzysztofik, Michał; Strońska, Katarzyna; Bojacz, Paulina; Żak, Marcin; Pajerska, Katarzyna (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Luge is a winter Olympic sport. The level of performance in luge depends on the cumulative time of runs (typically two) performed on the track. The fastest times of the best male lugers on the Königssee luge track in Germany are around 49 seconds, with the speeds reaching 140 km per hour. Aim of Study. The aim of the present study was to examine the pattern of internal movement structure of the push and paddle phases of the luge start in a group of Polish national elite lugers, with regard to the speed at which these motor tasks are performed. Material and Methods. The study examined the performance of six male members of the Polish National Luge Team. The study participants were randomized. The study was carried out on the Königssee luge track in Germany. The lugers’ motor activity was measured in six muscles: anterior deltoid (AD), biceps brachii (BB), triceps brachii (TB), latisimuss dorsi (LD), flexor carpi ulnaris (FCU), and trapezius (T). Results. The repeated measures ANOVA for peak muscle activity between two speeds of the push phase revealed statistically significant intragroup differences for the TB (F = 21.232; p = 0.001) and LD (F = 23.412; p = 0.001) muscles. The paddle phase revealed statistically significant intragroup differences for the LD (F = 34.121; p = 0.001), T (F = 22.111; p = 0.001) and TB (F = 19.211;p = 0.001). Conclusions. The results of the study show that a more effective use of the latisimuss dorsi, triceps brachii and trapezius muscles substantially improves the speed of the luge start.
Keywords: muscle activity; internal structure; activity index; luge